La circulation d’imprimés anglais : une fuite dans le système ibérique de contrôle des connaissances sur le Nouveau Monde - Roxana Nakashima (Nuevo mundo - Mundos Nuevos, 2013)
The last decades of the sixteenth century were characterized by a hostile relationship between the Iberian and the English crowns. In Spanish America, English corsairs attacked and fought the power of Phillip II. Underneath the pillages and the destructions, another kind of conflicts also existed. We will analyze different aspects related to the circulation of information on America, specially the Castilian laws that regulated it, as well as the ways in which the English corsairs affected it: by their presence on American soil and by obtaining and spreading information to be published, also by intercepting administrative correspondence and finally through the introduction of forbidden printed works.